miR-26a-5p/ADAM17-Mediated Proteolysis of TREM2 Regulates Neuroinflammation in Hypertensive Mice Following Lead Exposure - Yuran Wang; Zeming Wang; Han Hao; Yuwei Zhao; Jian Wang; Weixuan Wang (Toxics)
Hypertension is not merely a vascular disorder but a significant risk factor for neural impairment. Moreover, healthcare for the hypertensive population with environmental or occupational pollutants has become an issue of increasing concern in public health. As a traditional neurotoxic heavy metal, Pb exposure results in neuroinflammation as well as neurodegenerative diseases. The current study aimed to investigate the mechanisms of neuroinflammation in hypertensive mice exposed to Pb. We demonstrated that hypertension exacerbated Pb-induced neuroinflammation in the prefrontal cortex (PFC), hippocampus, and hypothalamus, as evidenced by increased levels of proinflammatory cytokines (IL-6 and TNF-α) and decreased levels of anti-inflammatory cytokines (CD206 and IL-10). Additionally, hypertension enhanced the neuroinflammatory response in microglia, as indicated by similar changes in cytokine expression in an in vitro cell model. Importantly, we found that TREM2, a key regulator of microglial inflammation, was downregulated in hypertensive mice with Pb exposure. This decline in TREM2 expression was associated with increased proteolysis of TREM2 by a disintegrin and metalloproteases 10 (ADAM10) as well as a disintegrin and metalloproteases 17 (ADAM17), in which ADAM17 was verified as the main cleavage enzyme in terms of TREM2 proteolytic cleavage in hypertensive mice following Pb exposure. Furthermore, we identified miR-26a-5p as a potential regulator of ADAM17 expression, suggesting a potential mechanism for the downregulation of TREM2 in this context. Our findings provided new insights into the complex interplay between hypertension, Pb exposure, and neuroinflammation as well as highlight the potential role of TREM2, ADAM17, and miR-26a-5p as therapeutic targets for neuroinflammation in hypertensive populations with Pb exposure.